Comparison of proteomic approaches used for the detection of potential biomarkers of Alzheimer's disease in blood plasma. Issue 22 (3rd October 2021) - Smirnova, Tatiana Anatolievna; Viskin, Anton; Hoskova, Martina; Habartova, Lucie; Setnicka, Vladimir; Cejnar, Pavel; Kuckova, Stepanka
Abstract: At present, Alzheimer's disease is detected mainly using psychological tests, which can only confirm the disease in its more advanced phases. Therefore, bioanalytical possibilities for detecting this disease earlier are being investigated. To date, the results of analyses, which focus mainly on the study of lipids and proteins either in cerebrospinal fluid or much less often in blood plasma, do not provide satisfactory results. In addition, cerebrospinal fluid sampling is uncomfortable for the patients and involves many health risks. In this work, we deal with proteomic analysis using Matrix‐Assisted Laser Desorption/Ionisation—Time of Flight and Liquid Chromatography coupled to tandem Mass Spectrometry of blood plasma with a focus on various ways of preanalytical sample treatments. This should lead to results improvement and facilitate the subsequent evaluation using principal component analysis and partial least squares discriminant analysis. The obtained results indicate the direction of further research, namely the study of interactions between proteins and lipids contained in blood plasma. These substances may be regarded as potential biomarkers allowing for the diagnosis of Alzheimer´s disease even in its early stages.